Cognitive Level Distribution in Bupena English Textbook: A SOLO Taxonomy Analysis - Tri Aliyah; Nursalim Nursalim; Fitri Arniati; Jusrianto AS (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study investigates the distribution of lower-order and higher-order thinking skills (LOTS–HOTS) in the evaluation questions of the English Bupena textbook by integrating Bloom's Revised Taxonomy and the SOLO Taxonomy as a dual analytical framework. It aims to examine the extent to which textbook evaluation tasks support students' critical and higher-order thinking skills in line with curriculum demands. A total of 81 evaluation items were analyzed using qualitative descriptive content analysis supported by quantitative frequency calculations. Each item was systematically coded according to Bloom's cognitive dimensions and SOLO structural complexity, with reliability ensured through inter-coder agreement. The results show that 80.25% of the questions are LOTS, while only 19.75% are HOTS. Most items fall at the unistructural and multistructural levels, indicating limited opportunities for relational and extended abstract reasoning. These findings suggest that the textbook predominantly promotes surface-level learning rather than deep cognitive Engagement. The study highlights the value of multidimensional cognitive frameworks for evaluating the quality of EFL textbook assessment.